Distributional Effects in Household Models: Separate Spheres and Income Pooling. - Browning, Martin; Chiappori, Pierre-André; Lechene, Valérie (Economic Journal, 2010)
We derive distributional effects for a non-cooperative alternative to the unitary model of household behaviour. We consider the Nash equilibria of a voluntary contributions to public goods game. Our main result is that, in general, the two partners either choose to contribute to different public goods or they contribute to at most one common good. The former case corresponds to the separate spheres case of Lundberg and Pollak (1993). The second outcome yields (local) income pooling. A household will be in different regimes depending on the distribution of income within the household. Any bargaining model with this non-cooperative case as a breakdown point will inherit the local income pooling. We conclude that targeting benefits such as child benefits to one household member may not always have an effect on outcomes.